(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Dental and oral health problems are common in children worldwide, particularly among primary school-aged children from 6-12 years old. This age group is in the mixed dentition stage and it is critical to maintain the health of primary teeth, which play an important role in the development of the permanent dentition. However, children in this age range often have poor oral hygiene habits and a high affinity for cariogenic foods. The aim of this literature review is to summarize the most prevalent dental and oral health problems affecting primary school children and discuss strategies for management and prevention. Based on the articles reviewed, dental caries and periodontal disease are the most common oral health issues in this population, primarily due to plaque accumulation. Additional problems include traumatic dental injuries, malocclusion, and premature loss of primary teeth. Preventive approaches at both the individual and community level are essential, including proper oral hygiene instruction, topical fluoride application, sealants, and regular dental check-ups. Parents and schools must work together to establish healthy habits and ensure access to professional dental care. With timely intervention and a focus on prevention, many of these oral health problems can be avoided, promoting better quality of life for children as they transition to adulthood.